Social sustainability of post-disaster: how teachers enable primary school students to be resilient in times of Ranau earthquake - Soon Singh Bikar Singh; Balan Rathakrishnan; Mohammad Rahim Kamaluddin; Norruzeyati Che Mohd Nasir; Mohd Azrin Mohd Nasir (MDPI AG, 2021)
The Ranau Earthquake that struck on 5 June 2015, February 2018, and April 2021, were a new disaster in Sabah and caused many Sabahan to panic. The unpredicted disaster also caused a serious impact on all aspects of life in Sabah. The earthquake has caused severe damage to eight primary schools in the vicinity of the epicenter, although no casualties were reported. However, the disaster has deep passing psychological effects among students. In this study, we examine how the primary school teachers enabled the student to be resilient during and after the disaster. Based on the interviews with 16 primary school students, it was revealed that most of the teachers used WhatsApp to support resilience during and after the earthquake. Interviews with 16 primary school teachers revealed there were two main reasons for them to communicate with students, namely, delivering emotional aid and monitoring their stress. Based on student interviews, five content categories of emotional support were identified: caring, reassuring, emotion sharing, belonging, and distracting. The main contribution of this study is that social media can be used as a spontaneous and proactive tool for supporting the student’s resilience during and after the earthquake trauma.